Increasing Of Student Learning Activities In Sociological Learning Using Differential Learning Models - Nursal, Yelliza (Master Program of Social Science Education of Universitas Negeri Padang, Indonesia, 2022)
The problem of low student activity in participating Sociology learning process. The types of activities experienced are: Students pay attention to the teacher when explaining lessons; Willing the students to ask and answer the questions; Students' interest in doing assignments; Courage of students in group presentations; As well as student activities in collaboration. The purpose of this study is to increase the sociology learning activities of class XII IPS 1 student of SMAN 1 Ranah Pesisir using the Differentiated Learning Model for the 2022/2023 school year. This type of research is Classroom Action Research (PTK) which is carried out in two cycles. Each existing cycle consists of three meetings. The first cycle consists for four stages: scheming, implementing, observation and reflection. The subjects of this study consisted of 29 students of class XII IPS 1. The Techniques used for collecting the data through observations and interviews. The collected data were analyzed using qualitative methods. The results showed that the first cycle of student learning activity was 64.60% and in the second cycle increased 20.66% to 85.26%. An indicator of the success of learning activities in this study was an increase in the average score of students' sociology learning activities from the first cycle to the second cycle. Another indicator of success in this study if the number of students who are active in learning activities in one class reaches 75%.